2008
DOI: 10.1186/1471-2148-8-187
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of susceptibility to parasites

Abstract: BackgroundThe antagonistic co-evolution of hosts and their parasites is considered to be a potential driving force in maintaining host genetic variation including sexual reproduction and recombination. The examination of this hypothesis calls for information about the genetic basis of host-parasite interactions – such as how many genes are involved, how big an effect these genes have and whether there is epistasis between loci. We here examine the genetic architecture of quantitative resistance in animal and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 19 publications
(18 reference statements)
9
99
0
Order By: Relevance
“…When we scanned for additional QTL that modify the effect of the first set of QTL we identified, we were able to identify an additional locus that reversed the effect of a resistance gene. Wilfert and Schmid‐Hempel (Wilfert & Schmid‐Hempel 2008) reviewed published studies that have identified QTL for host resistance in animals and plants, and found that epistatic interactions were presented in the majority of cases and were responsible for a substantial amount of the explained variance. Our results suggest that in our system epistatic interactions do occur, but they are unlikely to have such pervasive effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When we scanned for additional QTL that modify the effect of the first set of QTL we identified, we were able to identify an additional locus that reversed the effect of a resistance gene. Wilfert and Schmid‐Hempel (Wilfert & Schmid‐Hempel 2008) reviewed published studies that have identified QTL for host resistance in animals and plants, and found that epistatic interactions were presented in the majority of cases and were responsible for a substantial amount of the explained variance. Our results suggest that in our system epistatic interactions do occur, but they are unlikely to have such pervasive effects.…”
Section: Discussionmentioning
confidence: 99%
“…We used PCR to genotype the founder lines and selected RILs for polymorphisms in the genes ref(2)p and CHKov1 that have been previously associated with virus resistance. Two flanking universal primers (ref2p‐P1‐F 5′‐CTCACCCAGCTGCACTTGTA‐3′, ref2p‐PS1‐R 5′‐TGTTGCAATCTTTGCGACTC‐3′) and a specific primer for each allele (susceptible allele: ref‐a1‐Forward 5′‐GGATGCCCTCCCAGAATTA‐3′; recessive allele: ref‐a1‐Reverse 5′‐ CGACGCAATRYGGTGTATCC‐3′) were used to genotype ref(2)p (Wilfert & Schmid‐Hempel 2008). A forward primer CHK_F (59 CTCTTGGCTCCAAACGTGAC 39) and reverse primer CHK_R (59 AAGGCAAACGACGCTCTT 39) were used to detect the absence of the Doc1420 element in CHKov1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of trait variance explained by a QTL is essentially a question of genetic architecture, i.e. of the number, effect size and allelic interactions of all the loci affecting the trait [203].…”
Section: The Importance Of Understanding Genetic Architecturementioning
confidence: 99%
“…Second, mapping studies do not necessarily provide a reliable guide to the contribution made by a QTL to the genetic variance of a quantitative trait in natural populations, because the extent of this contribution depends critically upon allele frequencies, which will differ among populations [207]. Finally, there is increasing evidence that epistatic effects (interactions among loci) explain a substantial portion the genetic variance in many quantitative traits [203,206,208]; this means that the effect of any particular QTL will vary depending on the genetic background.…”
Section: The Importance Of Understanding Genetic Architecturementioning
confidence: 99%